Vilniaus miesto gyventojų telkimo į bibliotekas eksperimentas ir pirminiai jo rezultatai - Rimša, Vytautas (Knygotyra, 1990)
A series of experiments on directing town people to libraries was carried out under the program of sociological-psychological research on the theme "The role of libraries in developing and satisfying professional and spiritual interests of young workers." Between October 1, 1981, and December 31, 1981, a test experiment was carried out in 23 departments of the Vilnius Central Library and its branches. Its purpose was to ascertain the importance of a newspaper announcement in the form of an invitation/information in directing young workers and other categories of readers to libraries. The total data accumulated over the experimental and pre-experimental control period (1980) covered 3,263 working days, 10,372 new readers (of whom 2,112 were workers), and 143,157 visits to the library. The preliminary results of the analysis of the general tendencies in the development of these processes have shown that the announcement had a practical impact in the communication system "Newspaper - reader - library." The announcement had particularly enhanced the dynamics of these processes: over the period of the experiment, the direction of workers to libraries increased by 8.49 percent, the number of new readers by 16.99 percent, and the number of visits to the library by 15.77 percent, as compared with the pre-experimental control period. Besides, the experiment has tested in practice and confirmed the correctness of the methodological conception underlying it as well as its technological model.